First we have to take a look at the expression f(x + 1). This represents an horizontal translation. So this is the first transformation:
1. Horizontal translation
Now we can see that we have to multiply f(x + 1) by -1. This represents a reflexion on the y-axis
2. Reflection on y-axis
Finally we can see that -f(x + 1) is added by 3 units. This represents a vertical translation:
3. Vertical translation
Answer:
1. Horizontal translation
2. Reflection on y-axis
3. Vertical translation
Now let's see the final function:
f(x) = 2x - 5
f(x+1) = 2(x + 1) - 5
f(x+1) = 2x + 2 - 5
f(x+1) = 2x - 3
g(x) = -2x + 3 + 3
g(x) = -2x + 6
So let's plot f and g on the same reference system: